POTRET REPRESENTASI GERAKAN PEREMPUAN DALAM MENDORONG KETAHANAN PANGAN DI PROVINSI BANTEN - Gilang Ramadhan; Ika Arinia Indriyany (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2022)
This research was conducted to see the progress of the women's movement in Banten. The women's movement arises because of the political opportunity structure that provides space for women to maximize the resources they have to form social movements. As a representation of the women's movement, GOW has a role in realizing women-friendly policies and food security through one of the organizations under it, namely KWT which focuses on the empowerment of women farmers. This study uses a descriptive qualitative approach, while the results of the research are descriptions of a phenomenon in different contexts so that the conclusions of each individual will be different depending on the point of view used. In the midst of gender mainstreaming in social movements, this research is expected to open the veil of space for the women's movement, especially in the context of encouraging women-friendly policies and maximizing the role of women in promoting food security.